Microscopic Analysis of Severe Structural Rearrangements of the Plant Endoplasmic Reticulum and Golgi Caused by Overexpression of Poa semilatent virus Movement Protein. (4th January 2012) - Solovyev, Andrey G.; Schiemann, Joachim; Morozov, Sergey Y.
Abstract : Cell-to-cell transport of plant viruses is mediated by virus-encoded movement proteins and occurs through plasmodesmata interconnecting neighboring cells in plant tissues. Three movement proteins coded by the "triple gene block" (TGB) and named TGBp1, TGBp2 and TGBp3 have distinct functions in viral transport. TGBp1 binds viral genomic RNAs to form ribonucleoprotein complexes representing the transport form of viral genome, while TGBp2 and TGBp3 are necessary for intracellular delivery of such complexes to plasmodesmata. Recently, it was revealed that overexpression of Potato virus X TGBp3 triggers the unfolded protein response mitigating the endoplasmic reticulum (ER) stress leading to cell death if this protein reaches high levels in the ER. Here we report microscopic studies of the influence of the Poa semilatent hordeivirus TGBp3 overexpressed in Nicotiana benthamiana epidermal cells by particle bombardment on cell endomembranes and demonstrate that the protein C-terminal transmembrane segment contains a determinant responsible for vesiculation and coalescence of the endoplasmic reticulum and Golgi presumably accompanying the ER stress that can be induced upon high-level TGBp3 expression.